IMPLEMENTATION OF MANAGEMENT IN ISLAMIC EDUCATION AT MUHAMMADIYAH VOCATIONAL SCHOOL BERAU - Rahmawati, Rahmawati; Malli, Rusli; Asykur, Muamar; Temarwut, Taufik (JICSA : Journal of Islamic Civilization in Southeast Asian, 2023)
This study discusses Management Implementation in the context of Islamic education at SMK Muhammadiyah Berau. The scope of the study includes key aspects of management, such as Planning, Organizing, Implementing, and Controlling. The purpose of the study was to analyze the effectiveness of management in improving the quality of Islamic education at SMK Muhammadiyah Berau. Research methods involve literature study, observation, interviews, and documentation. The results showed the positive impact of Management Implementation on the quality of Islamic Education at SMK Muhammadiyah Berau. This is evidenced by increasing efficiency, student participation, and quality of learning. The conclusion confirms that implementing effective management can be the key to the success of Islamic education at SMK Muhammadiyah Berau, positively contributing to the development of students' potential and ensuring the vision of competitive Islamic education